Comparison of the diversity and structure of the rhizosphere microbial community between the straight and twisted trunk types of Pinus yunnanensis - Li, Peiling; Zong, Dan; Gan, Peihua; Li, Hailin; Wu, Zhiyang; Li, Fahong; Zhao, Changlin; Li, Laigeng; He, Chengzhong (Frontiers in Microbiology, 2023)
Pinus yunnanensis is a major silvicultural species in Southwest China. Currently, large areas of low-quality P. yunnanensis stands, especially those with twisted trunks, severely restrict its productivity. Different categories of microbes are present in the plant rhizosphere region, which evolve alongside plants and environments and play an important role in the growth and ecological fitness of their host plant. Here, we assessed and compared the diversity and structure of the rhizosphere microbial communities between P. yunnanensis with two different trunk types—straight and twisted—by Illumina sequencing of 16S rRNA genes and internal transcribed spacer (ITS) regions. We collected the rhizosphere soil of 5 trees with the straight and 5 trees with the twisted trunk type in each of three sites in Yunnan province. The results showed that the available phosphorus in soil differed significantly between P. yunnanensis with straight and twisted trunks. Available potassium had a significant effect on fungi. Chloroflexi dominated the rhizosphere soils of the straight trunk type, while Proteobacteria was predominant in the rhizosphere soils of the twisted trunk type. Trunk types significantly explained 6.79% of the variance in bacterial communities. This study revealed the composition and diversity of bacterial and fungal groups in the rhizosphere soil of P. yunnanensis with straight and twisted trunk types, providing proper microbial information for different plant phenotypes.